Accessing uncultivated microorganisms : from the environment to organisms and genomes and back - Zengler, Karsten (Washington, D.C. : ASM Press, 2008)
includes index
Keywords: Microbial diversity; Microbial ecology; Microbiology; Environmental Microbiology; Bacteria; Cell Culture Techniques; Fungi; Genetics, Microbial; Microbiological Techniques